Angular development with TypeScript - Fain, Yakov; Moiseev, Anton (Manning Publications, 2019)
Whether you're building lightweight web clients or full-featured SPAs, Angular is a clear choice. The Angular framework is fast, efficient, and widely adopted. Add the benefits of developing in the statically typed, fully integrated TypeScript language, and you get a programming experience other JavaScript frameworks just can't match. Angular Development with TypeScript, Second Edition teaches you how to build web applications with Angular and TypeScript. Written in an accessible, lively style, this illuminating guide covers core concerns like state management, data, forms, and server communication as you build a full-featured online auction app. You'll get the skills you need to write type-aware classes, interfaces, and generics with TypeScript, and discover time-saving best practices to use in your own work.
Includes index. - Online resource; title from title page (Safari, viewed April 10, 2019)
Keywords: AngularJS (Software framework); Application software -- Development; Web applications -- Development; TypeScript (Computer program language); Logiciels d'application; Développement; Applications Web; Développement; TypeScript (Langage de programmation); Application software; Development